DESIGNING E-MODULE OF TRANSLATION AND INTERPRETATION USING KVISOFT FLIPBOOK MAKER FOR ENGLISH EDUCATION DEPARTMENT STUDENTS - Fitrani Dinda Fadilah; Nur Aisyah Zulkifli (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2024)
This study aimed to find out the module needed by students in translation and interpretation course and to design e-module using kvisoft flipbook maker. This research used a research and development (R&D) method using the ADDIE model. The data collection technique used is through a questionnaire, document list and validation sheet. This research was hold on July 06, 2023 at Department of English Education UIN SUSKA Riau. This study was conducted at UIN Suska Pekanbaru, Riau. The participants of this study for need analysis the data was given to 6th-semester EED students and teachers, in addition for validation the data was given to learning material expert and media expert. The result of this study shows that the students and teachers needed e-module as a tools in teaching and learning process. However, the module was based on syllabus that reflected curriculum in higher curriculum. Furthermore, the ICC reliability results obtained an individual value (single measure) of 0.113 or included in the poor category, while the average calculation results (average measure) obtained a value of 0.203 with a poor category.